Adjunctive Aspirin vs Placebo in Patients With Schizophrenia: Results of Two Randomized Controlled Trials. (22nd January 2021) - Weiser, Mark; Zamora, Daisy; Levi, Linda; Nastas, Igor; Gonen, Ilan; Radu, Paull; Matei, Valentin; Nacu, Anatol; Boronin, Larisa; Davidson, Michael; Davis, John M
Abstract: Two previous randomized controlled trials (RCTs) suggested that adjunctive aspirin is efficacious in treating schizophrenia. We conducted two 16-week double-blind randomized placebo-controlled RCTs of adjunctive 1000 mg aspirin vs placebo in schizophrenia. Study 1 included 200 patients, with Positive and Negative Syndrome Scale (PANSS) total score as the primary outcome. Study 2 included 160 patients with C-reactive protein (CRP) >1 mg/L at baseline; the primary outcome was PANSS-positive score. Dropout rates for aspirin/placebo were 12% in study 1 and 20% in study 2. Differences in outcome between aspirin and placebo were calculated with linear regression, adjusting for the baseline value of the outcome. No statistically significant between-group differences were found in primary or secondary outcomes in either study. Study 1: mean difference in PANSS at 16 weeks was −3.9 (95% CI: −8.4 to 0.5, P = .10, effect size (ES) = −0.25) and at 8 weeks was −3.5 (95% CI: −7.5 to 0.5, P = .11, ES = −0.22). Study 2: mean difference in PANSS at 16 weeks was 0.3 (95% CI: −4.1 to 4.7, P = .90, ES = 0.02) and in positive PANSS was 0.5 (95% CI: −1.0 to 2.1, P = .50, ES = 0.11). A meta-analysis of these data with the existing studies, excluding one with large baseline differences in total PANSS, found that the overall estimate of the effect of adjunctive aspirin on the PANSS total score comparing group means at the end of the study was −2.9 (95% CI: −6.6 to 0.7; P = .21), favoring aspirin. Our studies and meta-analysis failed to find a statistically significant improvement in the symptoms of schizophrenia from adjunctive aspirin therapy in comparison to placebo in schizophrenia. Trial registration: study 1: Clinicaltrials.gov: NCT01320982; study 2 (high CRP): EudraCT Number: 2014-000757-36.